Mitochondrial dysfunction and Alzheimer’s disease: pathogenesis of mitochondrial transfer - Wei, Yun; Du, Xinlei; Guo, Hongling; Han, Jingjing; Liu, Meixia (Frontiers in Aging Neuroscience, 2024)
In recent years, mitochondrial transfer has emerged as a universal phenomenon intertwined with various systemic physiological and pathological processes. Alzheimer’s disease (AD) is a multifactorial disease, with mitochondrial dysfunction at its core. Although numerous studies have found evidence of mitochondrial transfer in AD models, the precise mechanisms remain unclear. Recent studies have revealed the dynamic transfer of mitochondria in Alzheimer’s disease, not only between nerve cells and glial cells, but also between nerve cells and glial cells. In this review, we explore the pathways and mechanisms of mitochondrial transfer in Alzheimer’s disease and how these transfer activities contribute to disease progression.